Integrating Religious and Psychological Constructs: A New Scale for Measuring Panca Jiwa Pondok in Islamic Boarding Schools - Aziz, Akbar Nur; Abd. Madjid; Raden Partino (Universitas Muhammadiyah Yogyakarta, 2025)
Character education in Islamic boarding schools (pesantren) plays a very important role in shaping the morals and personality of students. However, there is often no standardized and scientific instrument to measure these character values. This study aims to develop psychological indicators of Panca Jiwa Pondok, build a scale based on these indicators, and assess the validity and reliability of the scale. Panca Jiwa Pondok refers to five core values that form the foundation of character education in pesantren: sincerity, simplicity, independence, Islamic brotherhood, and freedom. This study uses a deductive technique, starting from the concept of dimensions to indicators in order to build a new scale. The instrument is designed with a religious-psychological approach, based on theoretical constructs derived from pesantren values, personality theory, and positive psychology. The trial was conducted on 103 students at Pondok Pesantren Al-Kamal Gombong in Kebumen, a modern pesantren that consistently applies the Panca Jiwa Pondok values. The validity test results show that of the 100 initial items, 92 items were declared valid based on a Pearson correlation > 0.197 and a significance value < 0.05. The scale's reliability shows high internal consistency with a Cronbach's Alpha value of 0.925. The results of exploratory factor analysis (EFA) identified five main factors consistent with the initial structure. This study shows that pesantren values can be measured scientifically and standardized, providing a basis for developing character assessments based on Islamic values. This instrument is expected to strengthen character education in pesantren and psychometrics based on local wisdom.